Pengembangan Mesin Pencacah Plastik Menggunakan Sistem Transmisi Gearbox - Abidin, Zainal; Basuki; Munib Rosadi, Mohammad; Arif Irfai, Mochamad; Eka Pramitasari, Retno (UNHASY, 2022)
The development of a plastic waste chopper machine with a gearbox transmission system was carried out because in previous studies there were still shortcomings, namely not being able to operate optimally because during the enumeration of plastic waste there was often a slip on the v-belt. So that this development is carried out using a gearbox transmission system so that the rotation when chopping is more leverage. The research method used is the R&D (research and development) method, a method or step to produce new products or develop existing products, and is used to test the effectiveness of the product. For engine specifications, it uses an electric motor with a speed of 1400 rpm, and a gearbox transmission system with a ratio of 1:50 as a transmission between the motor and the blade shaft. This study uses a type of PET plastic glass waste to be chopped. The results of the minimum engine speed of 16.6 rpm, gearbox output rotation of 28 rpm, rotation of the knife shaft 27 rpm, the value of the force on the count of 9.8 N, the pulley rotation of 1200 rpm, the ratio of the chain rotation speed of 1.037 and the number of connected sprockets. the gearbox has 46 teeth, while the sprocket connected to the blade shaft has 44 teeth. So that the resulting engine capacity is 1.02 kg/hour. In addition to the results of machine calculations, machine validation tests were also carried out that for the engine design assessment of 81.25% with very good criteria, engine function of 91.6% with very good criteria, while the calculation of machine capacity was 85% with very good criteria.